Bi-Atrial Primary Cardiac Lymphoma: a rare entity - Ngow, Harris Abdullah (Elsevier, 2010)
Primary cardiac lymphoma is a rare disease which mainly found in elderly men. It is usually a B-Cell non- Hodgkin’s lymphoma which primarily located in the heart and may involve the pericardium. The common presentations include massive pericardial effusion and heart failure. Clinical diagnosis is often delayed in these patients and prognosis is dismal. We report a case of a 70-year-old man presented with congestive cardiac failure and constitutional symptoms. A computed tomography of the chest showed two large right and left atrial masses. Echocardiographic study demonstrated that the tumor was in both atria with infiltration into the left ventricle. The diagnosis was confirmed by lymph node excision. The patient was started on chemotherapeutic agents but unfortunately succumbed to the disease 18 days later. Although, the prognosis of primary cardiac lymphoma remains poor, early diagnosis may alter the clinical course.